ANALYSIS OF VILLAGE FUND MANAGEMENT ON DEVELOPMENT AT PALALAKKANG VILLAGE - Muchriady Muchran; Firman Syah; Nuryahya Nuryahya; Murniady Muchran (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2022)
This study aims to determine how the management of the village fund management on the development of Desa Palalakkang. The type of research used is the qualitative research metode.The processed data is the result of interviews with palalakkang village staff. Data colettion methods used in this study is observation, interview, and documentation. The data source used are primary data sources and secondary data sources. The results showed that the vilage fund management on the development of Desa Palalakkang was quite effective based on UUD No. 6, 2014 and developed with the regional minister of the state No. 133, 2014.